2023
DOI: 10.3390/bioengineering10040464
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Photodynamic Therapy on CAM-Grown Sarcomas

Abstract: Resection margin adequacy plays a critical role in the local control of sarcomas. Fluorescence-guided surgery has increased complete resection rates and local recurrence-free survival in several oncological disciplines. The purpose of this study was to determine whether sarcomas exhibit sufficient tumor fluorescence (photodynamic diagnosis (PDD)) after administration of 5-aminolevulinic acid (5-ALA) and whether photodynamic therapy (PDT) has an impact on tumor vitality in vivo. Sixteen primary cell cultures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…In two studies, 3D cellular xenografts obtained from MFS cells (MUG-myx1 and MFS-SN1) were implanted in CAM to test the efficacy of photodynamic therapy for control of local recurrence in soft tissue tumors. In both cases, results demonstrated that photoactivation of the photosensitizer 5-aminolevulinic acid (5-ALA) greatly reduced xenograft volume [69,78].…”
Section: Cell Line-derived Xenograft Cell Line-derived Xenograft In Cammentioning
confidence: 99%
“…In two studies, 3D cellular xenografts obtained from MFS cells (MUG-myx1 and MFS-SN1) were implanted in CAM to test the efficacy of photodynamic therapy for control of local recurrence in soft tissue tumors. In both cases, results demonstrated that photoactivation of the photosensitizer 5-aminolevulinic acid (5-ALA) greatly reduced xenograft volume [69,78].…”
Section: Cell Line-derived Xenograft Cell Line-derived Xenograft In Cammentioning
confidence: 99%